Answer:
If the n-th term of a sequence be , t(n) equal to
then the 5-th term is 27 but if the n-th term is (2n -n) then the 5-th term is 5.
Step-by-step explanation:
If the n-th term of a sequence be , t(n) =
![2^(n) - n](https://img.qammunity.org/2020/formulas/mathematics/high-school/11fefs0s7urojjvxkf36af8ppxv5cngtj4.png)
then, the 5-th term is given by, t(5) =
![2^(5)- 5](https://img.qammunity.org/2020/formulas/mathematics/high-school/8xgqufkmiwrqhdssddbe7lnn2ris7xiqm4.png)
= 32 - 5
= 27
If the n-th term of a sequence be , t(n) = 2n - n = n
then, the 5-th term is given by, t(5) = 5